2008
DOI: 10.1016/j.joca.2007.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Lateral trunk lean explains variation in dynamic knee joint load in patients with medial compartment knee osteoarthritis

Abstract: Gait kinematics, particularly lateral trunk lean, explain substantial variation in dynamic knee joint load in patients with medial compartment knee osteoarthritis. While largely ignored in previous gait studies, the effect of lateral trunk lean should be considered in future research evaluating risk factors and interventions for progression of knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
142
5
10

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(166 citation statements)
references
References 47 publications
9
142
5
10
Order By: Relevance
“…First, we report and compare frontal plane trunk lean angles. Lateral trunk lean is receiving increased attention in the knee OA literature due to its common observation clinically, as well as its beneficial effect on medial compartment knee joint loading (13,14). Our findings suggest that the amount of lateral trunk lean over the affected knee increases with increasing disease severity.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…First, we report and compare frontal plane trunk lean angles. Lateral trunk lean is receiving increased attention in the knee OA literature due to its common observation clinically, as well as its beneficial effect on medial compartment knee joint loading (13,14). Our findings suggest that the amount of lateral trunk lean over the affected knee increases with increasing disease severity.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, biomechanics at the hip, pelvis, and trunk have all been shown to affect dynamic joint loading at the knee (11)(12)(13)(14). The importance of these proximal joints is highlighted by findings from Chang et al (12), which showed that increased internal hip abduction moments (equivalent to external hip adduction moments) attributed to higher hip abduction strength were protective against OA progression in the knee over an 18-month period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy has been evaluated in 2 studies of healthy young individuals, both demonstrating significant load reductions (10,21). Increasing trunk lean is postulated to modify knee load by changing the frontal plane center of mass location, subsequently reducing the ground reaction force lever arm at the knee and thus the KAM (22). Although research shows promising results, selective performance of this modification and effective load reduction is yet to be demonstrated in the medial knee OA population.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their influence on knee joint loading, we focused on the knee adduction moment and variables frequently reported to influence it, including toe-out angle, lateral trunk lean angle, and walking speed. 19,22,33,34 We also determined the rate of loading using the vertical ground reaction force (GRF) data. 27,32 Based on the external knee adduction moment waveform throughout stance, we identified the peak knee adduction moment during the first half of stance and normalized it to body weight and height (percent body weight × height).…”
Section: Outcome Measuresmentioning
confidence: 99%